ABOUT LUKMON BORIKHAN'S NOVEL "IMAM MOTURIDI" (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
The role of artistic works in conveying the country's past and great history to the young generation is incomparable. In Uzbek literature, many historical works have been written and are still being written today. One of such works, the novel "Imam Moturidi" by Luqman Borikhan was warmly welcomed by readers. In his work, the writer tells about the life of Abu Mansur Moturidi, a great theological scientist who lived in the 9th-10th centuries, one of the miraculous founders of the science of the word, and the difficult path of the scholar.